Design of Sensor Node for Drainage Blockage Monitoring System - Kale, Navnath; Prashanth, S. K.; Murthy, H. S. Niranjana; Keerthi, P.; Gurav, Yogesh; Babu P., Suresh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Monitoring the drainage systems is essential for maintaining a clean city. The truth is that not all localities have a drainage monitoring crew. As a result, the drainage condition is irregularly monitored. Unreliable monitoring causes drainage to become blocked, which results in overflow and causes flooding. This article discusses the creation of SN’s for use in wireless sensor networks to keep an eye on conditions at various drainage system locations. In order to link with one another, some SN’s are placed at various predetermined locations. The gathered information will be put into a database that a geographic information system may display (GIS).Water levels in the drainage, water outflow, and the amount of rainfall in the area surrounding the drainage are the monitoring criteria. The drainage conditions should be continuously monitored in real time by this system, and the data should be stored correctly. The data presented by GIS is meant to serve as a guide when creating a drainage master plan for a specific area.